Synthesis and Characterization of Cadmium-Copper Oxide (CdCu2O4) Nanoparticles by Chemical Co-Precipitation Method in the Presence of Oleic Acid as a Surfactant - Abouzar Tahkor (Journal of Global Pharma Technology, 2017)
The present study intended to synthesize cadmium-copper oxide (CdCu2O4) nanoparticles by chemical co-precipitation method in the presence of oleic acidC17H33COOH as a surfactant to control the size of particles. The spherical CdCu2O4nanoparticles were synthesized with an average particle size of 44.79 nm at the calcination temperature of900˚C for 4 hours. The chemical co-precipitation method was utilized as an easy and inexpensive method to produce high-purity mixed oxides. The morphology, network parameters and particle size of the product was studied and characterized by Fourier transform infrared spectroscopy (FT-IR), X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) techniques. The XRD analysis showed the pattern of CdCu2O4corresponded to Perovskite structure and monoclinic symmetry. The average particle size synthesized by XRD almost matched with the particle size observed in SEM image. The results indicated that the amount of surfactant, pH and stirring rate of solution had a crucial role in the homogeneity and particle size of the product.Keywords: Cadmium-copper oxide nanoparticles, Co-precipitation method, nanoparticles, oleic acid, Surfactant.